OPERATING BEHAVIOR OF A PHOTOVOLTAIC-DRIVEN ELECTROLYSIS SYSTEM - Walter, Gero; Diel, Sergej; Rufino Júnior, Carlos Antônio; Schweiger, Hans-Georg; Valente de Bessa, Iury; Mallmann, Maíra; Kirsten Vidal de Oliveira, Aline; Odilio Dos Santos, Daniel; Rüther, Ricardo (Revista Brasileira de Energia Solar, 2024)
Increasing demand for clean and sustainable energy is always accompanied by the challenge of storage and transportation. Hydrogen is a promising solution for storing energy generated by solar photovoltaics (PV). The intermittent nature of PV power generation systems represents a particular challenge for coupled water electrolysis systems. Batteries can be connected in parallel with the power generation system to mitigate the intermittency of renewable sources and to reduce the nominal power of electrolyzers and, consequently, the costs. The analysis of operational behavior is the first stage of designing an algorithm for PV power generation systems composed of water electrolyzers connected with batteries in parallel with a PV power generation system. This algorithm can identify the optimal operational points for the operation. This paper analyzes the energy demand under real operating conditions of an Anion Exchange Membrane (AEM) electrolyzer and the energy required for startup. To achieve this objective, the behavior under various production rates and electrolyte temperatures following different durations of idle phases were examined. An analysis of the dynamic response was also carried out. Significant amounts of energy are required for startup, particularly during high production rates and cold starts. From an operating time of around 3 hours after starting, the startup energy no longer plays a major role. The fast dynamic response of AEM electrolyzers also makes it possible to follow the intermittent supply from PV systems. Based on this, the energy budget for hydrogen production can be determined over the operating time, considering the startup. These results can support the development of control algorithms for the optimal operation of these green hydrogen production systems.